Ceramic insulation coatings on very thin nb3sn wires for lts coils - Arda, Lütfi; Çakıroğlu, Ömer; Aktaş, Şahin (Marmara Üniversitesi Fen Bilimleri Dergisi, 2009)
Ceramic insulation coatings on very thin Nb3Sn wires which are 0.001 mm (0.004”) in diameter were investigated by reel-to-reel sol-gel dip coating system. Varying thickness from submicron to several of microns sol-gel zirconium based ceramic coating has been successfully applied to Nb3Sn wires at the National High Magnetic Field Laboratory. Ceramic insulations were prepared using solutions of Yttrium and Zirconium based organometallic compounds. The film thickness was controlled by number of coating, withdrawal speed and solution chemistry. Crack-free, dense and ~ 546 nm coating was obtained with appropriate dilution of solutions. The surface morphologies and microstructure of all samples were characterized by ESEM, DTA, TGA and XRD. Resistance was measured using of HP 4339 A High Resistance Meter.
Keywords: Nb3Sn wire, Sol-gel, Y2O3-ZrO2, Insulation, LTS coils